Resposta a estresses consecutivos em Saccharomyces cerevisiae - Costa, Ane Catarine Tosi (2017)
The yeast Saccharomyces cerevisiae yeast plays an important role in industry due to its high fermentative capacity. During fermentation, there are constant changes in the conditions of the medium, exposing the yeasts to a series of simultaneous or sequential stresses and an efficient adaptation can lead to increased productivity and a improvement of their fermentative performance. In S. cerevisiae, adaptation involves an organized mobilization of genes called environmental stress response (ESR). Hsp12 is a protein belonging to families of heat shock proteins (HSPs) and this, in addition to maintaining the internal organization of the cell and increasing the flexibility of the cell wall and plasma membrane, is used as a stress reporter gene because its induction is in Largely through ESR already being used as a marker of stress status in yeast. Thus, the present work outlined a protocol of consecutive stress studies in order to evaluate morphological modifications and production of Hsp12 protein in S.cerevisiae. The results showed a similar variation of size of the mother cells and daughters in successive stresses compared to the growth of these cells in medium without stress addition. Cell cycle arrest was also a characteristic observed in both cells in consecutive stresses. The production of Hsp12 was higher in response to osmotic stress compared to oxidative and alcoholic stress in the isolated treatments, but the concentration of this protein in the latter two increased when the cell was exposed to consecutive stresses. This increase may be justified by the cross-protection of the acquired cell after contact with a high osmolarity solution. The difference in the results of the response to isolated and successive stresses shows that this methodology is more efficient to understand the behavior of the cell, because it is similar to the environment in the fermentation tanks.